Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.3 Exercises - Page 125: 16



Work Step by Step

Using the quotient rule: $f’(x)=(\frac{u(x)}{v(x)})'=\frac{u'(x)v(x)-v'(x)u(x)}{(v(x))^2}$ $u(x)=(x-4); u'(x)=1$ $v(x)=(x+4); v'(x)=1$ $f'(x)=\frac{(1)(x+4)-(x-4)(1)}{(x+4)^2}=\frac{8}{(x+4)^2}$. $f'(3)=\frac{8}{(3+4)^2}=\frac{8}{49}$ Alternative way to find the derivative: The following is a trick that you will use to integrate some complicated functions later on. Make the numerator the same as the denominator by adding and subtracting the same number from the numerator as follows: $f(x)=\frac{x-4}{x+4}=\frac{x-4+8-8}{x+4}=\frac{(x+4)-8}{x+4}=\frac{x+4}{x+4}-\frac{8}{x+4}=1-\frac{8}{x+4}$ Now $f'(x)$ can be found using the Power Rule: $f'(x)=(1)'-(8((x+4)^{-1})')=\frac{8}{(x+4)^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.